Multimodality Imaging in Cranial Giant Cell Arteritis: First Experience with High-Resolution T1-Weighted 3D Black Blood without Contrast Enhancement Magnetic Resonance Imaging - Brittain, Jane Maestri; Hansen, Michael Stormly; Carlsen, Jonathan Frederik; Brandt, Andreas Hjelm; Terslev, Lene; Jensen, Mads Radmer; Lindberg, Ulrich; Larsson, Henrik Bo Wiberg; Heegaard, Steffen; Døhn, Uffe Møller; Klefter, Oliver Niels; Wiencke, Anne Katrine; et al. (Diagnostics (Basel), 2023)
In order to support or refute the clinical suspicion of cranial giant cell arteritis (GCA), a supplemental imaging modality is often required. High-resolution black blood Magnetic Resonance Imaging (BB MRI) techniques with contrast enhancement can visualize artery wall inflammation in GCA. We compared findings on BB MRI without contrast enhancement with findings on 2-deoxy-2-[18F]fluoro-D-glucose positron emission tomography/low-dose computed tomography (2-[18F]FDG PET/CT) in ten patients suspected of having GCA and in five control subjects who had a 2-[18F]FDG PET/CT performed as a routine control for malignant melanoma. BB MRI was consistent with 2-[18F]FDG PET/CT in 10 out of 10 cases in the group with suspected GCA. In four out of five cases in the control group, the BB MRI was consistent with 2-[18F]FDG PET/CT. In this small population, BB MRI without contrast enhancement shows promising performance in the diagnosis of GCA, and might be an applicable imaging modality in patients.